2021
DOI: 10.1088/1361-6463/abdf97
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of AC arc ignition on cold electrodes in atmospheric-pressure argon

Abstract: Since experiments cannot clarify the mechanism of current transfer to non-thermionic arc cathodes, this can only be done by means of numerical modelling based on first principles and not relying on a priori assumptions. In this work, the first quarter-period after the ignition of an AC arc on cold electrodes in atmospheric-pressure argon is investigated by means of unified one-dimensional modelling, where the conservation and transport equations for all plasma species, the electron and heavy-particle energy eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The experimental results confirm the statement obtained by modelling that secondary electron emission, induced by ions impinging on the electrode surface, of a positive space charge layer in front of the cathode and an adjacent ionization layer is starting the current transfer to cold cathodes. [38] A look at Table 2 discloses a quite different increase of the commutation time t c with decreasing applied voltage between the arc plasma and CEs consisting of different materials. The increase is lowest for graphite electrodes, which are uncovered with an oxide layer after polishing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results confirm the statement obtained by modelling that secondary electron emission, induced by ions impinging on the electrode surface, of a positive space charge layer in front of the cathode and an adjacent ionization layer is starting the current transfer to cold cathodes. [38] A look at Table 2 discloses a quite different increase of the commutation time t c with decreasing applied voltage between the arc plasma and CEs consisting of different materials. The increase is lowest for graphite electrodes, which are uncovered with an oxide layer after polishing.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results confirm the statement obtained by modelling that secondary electron emission, induced by ions impinging on the electrode surface, of a positive space charge layer in front of the cathode and an adjacent ionization layer is starting the current transfer to cold cathodes. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation confirms the role of secondary electron emission obtained by numerical modelling cold cathodes of high‐pressure arc plasmas. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation confirms the role of secondary electron emission obtained by numerical modelling cold cathodes of high-pressure arc plasmas. [36] The electron emissivity varies in general as a function of the position on the end face of the cathode. It is increased first of all by a locally enhanced secondary electron emission coefficient 𝛾 i and less distinctly by a locally lowered work function or by locally increased electric field strength in front of tips on the electrode surface.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the region of the strongest electron overpopulation appeared at the intersection of the plasma fringes and the electrode surface. Some other relevant studies can be read elsewhere [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%